Tetra – Amelia with Brachygnathia inferior in a Holstein- Friesian cross bred calf - Kumar, Vipan; Pal, Heigo; Kumar, Parveen (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
A case of live male calf with the congenital tetra – Amelia condition is reported in this paper. External examination of the calf revealed total absence of all the four limbs. On physical examination there is brachygnathia inferior, no other phenotypic anomalies were found, while post-mortem examination revealed the fully developed visceral organs.